Changes in workplace accommodations among employed Canadians with disabilities, 2017 to 2022 - Christoph Schimmele; Sung-Hee Jeon; Rubab Arim (Economic and Social Reports)
Work arrangements changed during the COVID-19 pandemic, as organizations switched to working from home on a large scale and used digital technologies to adapt to physical distancing mandates (Deng et al., 2020; Fuentes & Lindsay, 2023). About 20% of all employed Canadians aged 15 to 69 years were working primarily from home near the end of 2023, an increase from 7% shortly before physical distancing measures began in March 2020 (Morissette, 2024). It is largely unknown how changes to work arrangements since the onset of the COVID-19 pandemic have impacted persons with disabilities (PWDs) in Canada.